Mengkombinasikan Project-Based Learning dengan STEM untuk Meningkatkan Hasil Belajar Teknikal dan Karakter Kerja Siswa SMK - Amri, Muhammad Shafiul; Sudjimat, Dwi Agus; Nurhadi, Didik (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2020)
Project-based Learning (PjBL) and Science, Technology, Engineering, and Mathematics (STEM) are multidisciplinary learning. The combination of PjBL-STEM aimed to improve vocational high school students' technical learning results and working characteristics. Thus, students, after graduating, could compete in the working world. This research used secondary data review method, consisted of 17 international journals, 11 national journals, and three literature books. Based on the secondary data review, the combination of PjBL-STEM would be maximized if the teacher directly involved in the learning, where the teacher acts as inspiratory, motivator, and facilitator. Then, the PjBL-STEM learning was started from designing until result presentation that could improve the creativity and problem-solving skills. PjBL-STEM improved the hard skill in the form of technical learning results and soft skill in the form of working characteristics. Therefore, model integration of PjBL and STEM should be well-prepared. The learning strategy in each lesson must be designed well, and the assessment dimensions must be chosen thoroughly so that multidisciplinary learning could be well-realized in vocational high school in Indonesia.